2022
DOI: 10.3390/genes13091645
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Adipose Gene Expression Profiles between Male and Female Even Reindeer (Rangifer tarandus) in Sakha (Yakutia)

Abstract: Reindeer are native to harsh northern Eurasian environments which are characterized by long and cold winters, short summers, and limited pasture vegetation. Adipose tissues play a significant role in these animals by modulating energy metabolism, immunity, and reproduction. Here, we have investigated the transcriptome profiles of metacarpal, perirenal, and prescapular adipose tissues in Even reindeer and searched for genes that were differentially expressed in male and female individuals. A total of 15,551 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In particular, HOXD13 had the highest abundance among all uniquely expressed genes in the metacarpal adipose tissue (Additional File 3: S1). HOXD13 is a highly conserved gene belonging to the HOX family of genes and is responsible for morphogenesis, limb development and genital development [72,73]. In murines, the HOX gene family has been associated with cell differentiation toward adipogenesis [74],…”
Section: Discussionmentioning
confidence: 99%
“…In particular, HOXD13 had the highest abundance among all uniquely expressed genes in the metacarpal adipose tissue (Additional File 3: S1). HOXD13 is a highly conserved gene belonging to the HOX family of genes and is responsible for morphogenesis, limb development and genital development [72,73]. In murines, the HOX gene family has been associated with cell differentiation toward adipogenesis [74],…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome studies have shown that gene expression patterns in adipose tissue differ between breeds, sexes, and adipose tissue depots and, more recently, that there are differences in adaptation to extreme environments [9,73]. Here, we studied the transcriptome profiles of four adipose tissues from three native cattle breeds and one commercial breed, all of which originated from different geographical locations and climates.…”
Section: Discussionmentioning
confidence: 99%